Obesity in children with poorly controlled asthma: Sex differences1. Issue 9 (9th November 2012) - Lang, Jason E.; Holbrook, Janet T.; Wise, Robert A.; Dixon, Anne E.; Teague, W. Gerald; Wei, Christine Y.; Irvin, Charles G.; Shade, David; Lima, John J.
Abstract Background Obesity increases asthma risk, and may alter asthma severity. In adults, sex appears to modify the effect of obesity on asthma. Among children, the effect of sex on the relationship between obesity and asthma severity remains less clear, particularly when considering race. Objective To determine how obesity affects disease characteristics in a diverse cohort of children with poorly controlled asthma, and if obesity effects are altered by sex. Design We analyzed 306 children between 6 and 17 years of age with poorly controlled asthma enrolled in a 6‐month trial assessing lansoprazole for asthma control. In this secondary analysis, we determined associations between obesity and symptom severity, spirometry, exacerbation risk, airway biomarkers, bronchial reactivity, and airflow perception. We used both a multivariate linear regression and longitudinal mixed‐effect model to determine if obesity interacted with sex to affect asthma severity. Results Regardless of sex, BMI >95th percentile did not affect asthma control, exacerbation risk or airway biomarkers. Sex changed the effect of obesity on lung function (sex × obesity FEV1%, interaction P‐value < 0.01, sex × obesity FEV1/FVC, interaction P‐value = 0.03). Obese males had significantly worse airflow obstruction compared to non‐obese males, while in females there was no obesity effect on airflow obstruction. In females, obesity was associated with significantly greater FEV1 and FVC, and a trend toward reduced airway reactivity. Conclusions Obesity did not affect asthma control, airway markers or disease stability; however obesity did affect lung function in a sex‐dependent manner. In males, obesity associated with reduced FEV1/FVC, and in females, obesity associated with substantially improved lung function. Pediatr Pulmonol. 2013; 48:847–856. © 2012 Wiley Periodicals, Inc.